2000
DOI: 10.1590/s0104-42302000000300005
|View full text |Cite
|
Sign up to set email alerts
|

Causas e prognóstico da insuficiência renal aguda hospitalar em pacientes idosos

Abstract: RESUMO -OBJETIVOS. O objetivo deste estudo foiO aumento da expectativa de vida da população é uma razão óbvia para explicar o aumento da proporção de pacientes idosos admitidos em uma instituição terciária 1-3 . Ao mesmo tempo, observase uma maior incidência de insuficiência renal aguda (IRA) na população com idade mais elevada 4,5 , e três fatores afetando a hemodinâmica renal têm sido imputados para esta maior incidência: o próprio processo de envelhecimento renal, a maior freqüência de estados patológicos n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the sociodemographic analysis of this study, it was noted that the group over 60 years of age had a higher incidence of renal failure. This can be explained by the fact that with advancing age, the glomerular filtration rate decreases as part of the body aging process ( 9 , 16 - 17 ) . The analysis of the associations between comorbidities and acute renal failure in the literature is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In the sociodemographic analysis of this study, it was noted that the group over 60 years of age had a higher incidence of renal failure. This can be explained by the fact that with advancing age, the glomerular filtration rate decreases as part of the body aging process ( 9 , 16 - 17 ) . The analysis of the associations between comorbidities and acute renal failure in the literature is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, only KDIGO 3 had this association, with a three-fold higher chance of mortality for the individual. Admission of elderly people with AKI to the ICU was considered a risk factor for mortality in previously published data 6 , 18 . Our study demonstrated a twelve-fold increased risk for these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated a twelve-fold increased risk for these cases. Some studies on the elderly have described an association of oliguria with an increased risk of death 18 , 19 . However, this factor has not been evaluated in studies on nonagenarians.…”
Section: Discussionmentioning
confidence: 99%